Shared parenting: why our Justice System still ignores this form of coparenting? - de Mattos, Elsa (2024)
The aim of this article is to discuss the importance of shared parenting, pointing out its benefits for children. Initially, it considers the emergence of shared parenting in the USA, in the years 1970’/80’ and its expansion to various countries, associated with changes in women's participation in the world of work and a more equal distribution of childcare between parents. Next, the characteristics and dimensions of shared parenting are discussed, highlighting that it can occur in different forms of family organization and that caregivers share not only the responsibility for making decisions regarding their children, but also practice of daily childcare and education of their offspring. Shared parenting is discussed in the Brazilian context, pointing to the limitations to its application, even in light of changes brought about by Law 13.058/2014 (Shared Custody Law). In particular, it shows that practices and perceptions about shared parenting are still influenced by gender beliefs and stereotypes. It is clear that in Brazil there are still many obstacles to greater paternal involvement in childcare practices on a daily basis. Finally, we highlight Parenting Plans as tools for reorganizing family relationships after separation/divorce, making it an effective instrument for promoting shared parenting, communicating values and objectives for raising children, as well as the division of childcare and education tasks between caregivers.